Determination Of Lecturer Reception Using Analytical Hierarchy Process (AHP) - Hafizah Hanim; Jefril Rahmadoni (Journal of Applied Engineering and Technological Science (JAETS), 2020)
During this time, the selection of non permanent lecturers, parts staffing difficulties in selecting lecturers. The obstacle faced is the large number of applicants who register to become prospective lecturers. So that the staffing or the campus must give extra time to choose prospective lecturers so that lecturers can be obtained that fit the desired criteria. The AHP (Analytical Hierarchy Process) method is a method in the decision-making process, this method performs a hierarchical structure calculation where the top level in the hierarchy is the goal to be achieved then the hierarchy below in the form of criteria in achieving goals and the lowest level is the alternatives in achieving goals.